Triple eyebrows, Shiv Shanti Bhuvan - Ghosh, Ayan (Jio Institute, 2023)
Three semicircular eyebrows (a horizontal ledge extending outward above a window) emphasize the faceted corner at the intersection of Maharshi Karve Road and HT Parekh Marg, Shiv Shanti Bhuvan.